Evaluation Of The Effectiveness Of The Initial Flight Attendant Training Program In Garuda Indonesia Training Center - Chandra S Haratua Gultom; R. Madhakomala; Hamidah (Journal of Business and Behavioural Entrepreneurship, 2020)
The purpose of this study is to evaluate the training effectiveness on GITC by applying the four levels Kirkpatrick model consisting of reaction, learning, behavior & Results. This study is cross sectional, primary data was collected through interviews from different batches representing different levels of the Kirkpatrick model. Effectiveness of training at the different levels was being evaluated through construct/theme developed on the basis of literature review. For level one evaluation interviews were conducted from employees who had recently completed their training; for level 2,3&4 the respondents, who had completed same training about 3 months, 6 months and year earlier respectively. The results indicated that reaction of the participants were positive for training except duration was too short, secondly they have applied skills & knowledge which they had learnt from training. A positive consequence of the training is that most of the participants got promoted from their current designation with the improvement in their pay scales. Thus, the soft skills trainings were effective with the participants desiring more opportunities to attend soft skills training session at least quarterly basis, to further improve their skills and enhance their knowledge.